Prevalence and factors associated with tinnitus: data from adult residents in Guangdong province, South of China. (2nd December 2018) - Yang, Haidi; Cai, Yuexin; Guo, Huanping; Xiong, Hao; Sun, Yingfeng; Huang, Xiayin; Zheng, Yiqing
Abstract: There is a lack of national studies on tinnitus in China and data based on a large sample size from multiple areas of the country. A cross-sectional study was carried out in Guangdong province from October 2015 to February 2016. In the study, tinnitus was defined as the presence of ringing, buzzing or other sounds in the ears in the past one year. Fourteen districts in Guangdong Province were selected as the first-level cluster by using the sampling method of probability proportional to size (PPS). Two sub-districts in each first-level cluster were randomly selected as the second-level cluster by PPS method. The sample consisted of 3705 eligible people aged over 18 years old, which were also selected by the PPS methods. The prevalence of tinnitus was 10.4% in Guangdong Province. Age, region, educational background, hearing impairment, ear trauma, otitis media and self-health report were the main risk factors for tinnitus. Tinnitus is a common condition and a large population suffers from tinnitus in Guangdong province, south of China. Greater public awareness and understanding of the associated factors are required for further interventions of prevention and management of tinnitus in China.